Right sided infective endocarditis masquerading as pulmonary tuberculosis: a case report - Abdul Hadi, Azwanis; Khairuddin, Khairun'naim; Ismail, Mohd Nizamuddin (IIUM Press, 2022)
Right-sided infective endocarditis is not as common as left-sided infective endocarditis. The clinical signs and symptoms of right-sided infective endocarditis are subtle, making clinical detection more complex and easily leads to this diagnosis. We present a case of mild haemoptysis as a presentation of right-sided infective endocarditis but was initially misdiagnosed as pulmonary tuberculosis, which led to a delay in treatment. The patient had multiple visits to the health facilities (private clinic, government’s health clinic and hospital) and one admission to the hospital for recurrent cough, fever, and haemoptysis without any improvement. Later, he was diagnosed with right-sided infective endocarditis and was well after treatment. Delays in treatment can lead to an increased risk of permanent morbidity to the patient. This case report highlights the importance of a high index of suspicion and exploring other differential diagnoses of haemoptysis apart from pulmonary tuberculosis.